Return to play after COVID-19: a sport cardiologist`s view - Dores, H.; Cardim, N. (British Journal of Sports Medicine, 2020)
On March 2020, WHO has declared the coronavirus disease (COVID-19), caused by the virus severe acute respiratory syndrome coronavirus 2 outbreak, a pandemic. Young people can be affected by the disease, and some of them require hospital admission and intensive care.